Answer:
90.84
Step-by-step explanation:
49.7+41.14= 90.84
Answer:
24
Step-by-step explanation:
You input will always be your x so you just substitute x with 10 and simplify. Which is 30 minus 6, thus 24. :)
Answer:
The initial value of the function is <u>2</u>
The base of the function is <u>3</u>
The function shows exponential <u>growth</u>
Step-by-step explanation:
f(x) = 2(3^x)
Exponential functions are those with the following equation:
y = a*b^x
where a ≠ 0, b > 0 and b ≠ 1 and x is a real number.
<em>a</em> is the y-intercept and <em>b </em>is the base.
The initial value of the function is the same as the y-intercept
If <em>a</em> is positive, the function growth. If <em>a</em> is negative, the function decay
Answer:
Ray.
Step-by-step explanation:
Lines have no endpoints, while rays have 1 endpoint (:
The equation formula of the circle is (x-h)^2 + (y-k)^2 = r^2
where (h,k) the point of the center of the circle
and (r) is the radius of the circle
so if the center of the circle = (-2,-4)
by subs. in the formula we get (x-(-2))^2 + (y-(-4))^2 = r^2
then the equation will be (x+2)^2 + (y+4)^2 = r^2
now we want to define the radius of the circle r
since point (3,8) lay on the circle so we can
then subs. in the equation to get the radius
(x+2)^2 +(y+4)^2 = r^2
(3+2)^2 +(8+4)^2 = r^2
25 + 144 = r^2
r^2 = 169
r= 13
the radius of the circle is 13
so by subs in the equation we get
(x+2)^2 + (y+4)^2 = 169
so it is the first answer in the choices